Effect of the thermal treatment on the chemical components, sorption, and shrinkage properties of Tectona grandis juvenile wood - de Oliveira Lopes, Juliana; B. Cáceres, Claudia; E. Hernández, Roger; A. Garcia, Rosilei (Maderas. Ciencia y Tecnología, 2022)
The effect of thermal treatment on the chemical components, equilibrium moisture content (EMC), and shrinkage of teak juvenile wood was studied. Heartwood and sapwood samples were thermally-treated at 180 ºC and 200 ºC. Extractive, Klason lignin, holocellulose, and α-cellulose contents, as well as pH on untreated and thermally-treated woods, were determined. The EMC was reached at five relative humidity (RH) levels using saturated salt solutions: 86 % (KCl), 76 % (NaCl), 58 % (NaBr), 33 % (MgCl2), and 0 % (P2O5). Linear and volumetric shrinkages were calculated for all EMCs. The ratio of sorption (S), coefficient of shrinkage (h), and fiber saturation point (FSP) were also determined. Thermally-treated wood exhibited lower holocellulose and α-cellulose contents than untreated wood and increased acidity due to degradation of the hemicelluloses. The thermal treatment reduced the EMC of heartwood and sapwood. However, sapwood was more sensitive to RH variations than heartwood regardless of the treatment. Thermally-treated woods had higher hygroscopic and dimensional stabilities, and lower FSP than untreated wood. The thermal treatment did not affect radial shrinkage of the heartwood between 33 % and 86 % RH. Heartwood was more sensitive to the effect of the thermal treatment on shrinkage and degradation of cell wall polymers compared to sapwood.